Analysis of The Causes of The Delay in Loans for Members of The Melati Women's Cooperative in Sidoarjo City - Khafidhotun Zarro Azizah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Cooperative is an association or an organization consisting of each person who can go in and out like a member. Savings and loan cooperatives collect funds through their members and channel them back to cooperative members and the community. This will result in delays in loans to jasmine women's cooperatives. This study uses a descriptive qualitative method that describes the causes of delays in member loans in women's cooperatives. The results of this study indicate that the cause of delays in cooperative loans is because customers continue to delay payments which results in losses to the Jasmine Women's Cooperative and also many customers who are not in good faith and use these loans not according to their needs.